A dictionary of business and management. (Oxford [England] ; New York : Oxford University Press, 2009)
"This dictionary clearly defines the very latest terminology used in business and management, including wiki and the subprime lending crisis. Authoritative and comprehensive, it is an essential A-Z for students, teachers, professionals, and anyone needing clarification of commonly used business terms."--BOOK JACKET.
A dictionary of business and management -- Bankruptcy law (feature) -- Checklist for a business plan (feature) -- Assessment on damages (feature) -- Data protection act 1998 (feature) -- European Economic and Monetary Union (feature) -- The FTSE indexes (feature) -- International paper sizes (feature) -- Mortgage law (feature) -- The service economy (feature) -- Statement of terms of employment (feature).
Previous ed.: 2006.
Includes web resources.
Keywords: Management -- Dictionaries; Business -- Dictionaries; Betriebswirtschaftslehre -- 2; Wirtschaft -- 2